EU Concerns About Chinese Subsidies: What the Evidence Suggests - Frank Bickenbach; Dirk Dohse; Rolf J. Langhammer; Wan-Hsin Liu (Intereconomics, 2024)
China uses subsidies extensively to take a leading role in the global markets of green-tech products such as battery electric vehicles and wind turbines. Against the background of the current EU investigations into Chinese subsidies in these sectors, this article takes a careful look at the Chinese subsidy system and provides new data on direct government subsidies to leading Chinese producers of electric cars and wind turbines. Extensive government support has allowed Chinese companies to scale up rapidly, to dominate the Chinese market and to expand into foreign markets. The article concludes that the EU should use its strong bargaining power due to the single market to induce the Chinese government to abandon the most harmful subsidies.
Keywords: F13; O25; O53; 330; China; industrial subsidies; battery electric vehicles; wind turbines; railway rolling stock; EU; anti-subsidy proceeding